Effectiveness of Superficial Parotidectomy and Partial Superficial Parotidectomy for Benign Parotid Tumors - Asmatullah, Habibullah, Bashir Ahmad, Ahmad Shah, Nazeer Ahmad Sasoli, Muhammad Idrees Achakzai, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Bening parotid tumors are noncancerous growth occurring in parotid gland with various types. The treatment option varies from surgical excision (superficial and partial parotidectomy), observatory or radiation therapy. Objective: To compare the effectiveness of superficial parotidectomy and partial superficial parotidectomy for benign parotid tumors. Study design: Prospective study Place and duration of study: Department of ENT Head & Neck Surgery, Bolan Medical College, Quetta from 1st January 2023 to 1st August 2023. Methodology: One hundred and fifty patients post-diagnosis of benign parotoid tumors through Magnetic resonance imaging, echography, fine-needle biopsy, and computed tomography were enrolled. The patients were divided into two groups each with 75 patients in it depending upon superficial parotidectomy and partial superficial parotidectomy respectively. Surgical excision was performed according to superficial parotidectomy or partial superficial parotidectomy protocol. The hospital stay, operation time and complications formed and the complication rate was compared within both groups. Results: The mean age of the patients was 54.0±9.9 in superficial parotidectomy and 51.2±7.5 years in partial superficial parotidectomy group. The patient age was between 18-75 years with majority of the patients been males than females in both groups. Among the total patients enrolled a prolonged hospital stay was observed in superficial parotidectomy cases in comparison with partial superficial parotidectomy patients with a value of 6.6±2.2 vs 4.3±2.1 days respectively. The mean operative time was found to be significantly higher in superficial parotidectomy cases verses partial superficial parotidectomy with a value of 134.1±22.3 vs 93.1±20.9 minutes. There were 5.3% patients in superficial parotidectomy group which had a recurrence of tumor while only 2.6% of the partial superficial parotidectomy patients had recurrence occurred. Conclusion: Partial superficial parotidectomy is comparative more effective than superficial parotidectomy with reduced complication risk and decreased hospital and operational time. Keywords: Superficial parotidectomy, Partial superficial parotidectomy, Benign parotid tumors.